CATCH AND RELATIVE ABUNDANCE OF SOME SHARKS LANDING IN TANJUNG LUAR, LOMBOK - Agus Arifin Sentosa; Dharmadi Dharmadi (Pusbindiklat - LIPI, 2017)
Tanjung Luar is the center of shark fisheries in Indonesia because it has more shark catches than any other fish landing places in Indonesia. The aims of this study were to present the catch characteristics and the relative abundance of some sharks landing in Tanjung Luar, Lombok. Data were obtained through the interview with enumerators and from their daily monitoring record on the shark landing at Tanjung Luar, East Lombok during eleven months period from January to November 2015. Data statistics were calculated descriptively and presented as a percentage of relative abundance. The result shows the shark caught in 2015 has fluctuated monthly with the peak of catch occurred on September 2015. Total shark caught were about 237.5 tonnes and average landing per day was 1.4 tonnes. Species composition of overall catch comprised of 28 species which belong to 11 families. Among those species, Silky shark/Carcharhinus falciformis (42.06%), Blue shark/Prionace glauca (10.45%) and Blacktip shark/Carcharhinus limbatus (10.31%) were predominant as indicated having relative abundance more than 10%.